PERSEBARAN PEMILIH TETAP BERDASARKAN E-KTP DI WILAYAH KABUPATEN BATANG - Rindhi Fitri Sari; Bambang Agus Herlambang, Ahmad Khoirul Anam (Jurnal Komunikasi, 2024)
The general election is an important event in democratic life in Indonesia. Batang Regency is one of the regions in Indonesia that has a significant number of voters. In facing the 2024 Simultaneous Elections, Batang Regency Bawaslu has supervised the Open Plenary Meeting of the Recapitulation of the Updated Voter List (DPHP) and the Determination of the Temporary Voter List (DPS). This is done to ensure that the voter list used in the 2024 Simultaneous Elections is accurate and valid data. Problems identified include slow publication of E-KTPs, system disruptions, limited supporting facilities and infrastructure, and the large number of people who need E- KTPs. Spatial data in this project includes geographic information related to population locations recorded with e-KTP, such as geographic coordinates, administrative boundaries of sub-districts, villages, or RT/RW in Batang Regency. Non-spatial data is used to determine the attributes and characteristics of voters who remain registered, such as gender, age and education